A Decade in Review: The Evolving Epidemiology of HIV and AIDS in Nepal - Rajbahak, Aastha; Tamang, Aasta; Adhikari, Rejina (NPRC Journal of Multidisciplinary Research, 2025)
Background: HIV/AIDS remains a significant public health issue in Nepal, characterized by a concentrated epidemic among key populations. Despite a declining national prevalence, significant sub-epidemics persist, driven by complex socio-structural factors. A synthesis of the current evidence is crucial to inform the national goal of ending AIDS by 2030.Objective: This review aims to synthesize the current state of knowledge on the epidemiology of HIV and AIDS in Nepal over the last decade. It provides a comprehensive overview of the burden of infection, evolving trends, risk factors, and the national response, with particular attention to the structural determinants of vulnerability.Methods: A narrative review was conducted, synthesizing data from recent national surveillance reports, including the Nepal HIV/AIDS Strategy and Integrated Biological and Behavioral Surveillance (IBBS) surveys, and seminal peer-reviewed research by Nepali scholars. The analysis applied a structural-functional theoretical framework to interpret findings.Findings: The adult HIV prevalence in Nepal is low at 0.13%, but the epidemic is concentrated, with disproportionately high rates among key populations: People Who Inject Drugs (7.9%), transgender people (6.3%), Men Who Have Sex with Men (5.5%), and Female Sex Workers (1.5%). Labor migrants and their spouses form a critical bridge population. Research consistently shows that vulnerability is shaped by macro-level structural factors including poverty, gender inequality, stigma, and migration, which limit individual agency and create a disconnect between HIV knowledge and preventive practices. The national response has scaled up antiretroviral therapy (73% coverage) and targeted interventions, but challenges like stigma, inequitable access, and sustainable funding persist.Conclusion: HIV in Nepal is a concentrated epidemic sustained by high prevalence among key populations and fueled by deep-seated structural determinants. While the national response has made progress in treatment, a persistent gap between knowledge and practice underscores the need for interventions that address the underlying social, economic, and cultural drivers of transmission.Implementation: To end AIDS as a public health threat, Nepal must intensify combination prevention, systematically address stigma and discrimination, strengthen the integration of HIV services into primary healthcare, invest in strategic information to track emerging trends, and ensure financial sustainability through increased domestic investment.